Nasal Intubation via Laryngoscope in Maxillofacial Surgeries: Changes in Hemodynamic Parameters - Sharma, Archna; Sharma, Manish Kumar; Singh, Dara (Asian Journal of Medical Research, 2021)
Background: The purpose of the present study was to check the hemodynamic response of conventional nasal intubation in oral and maxillofacial surgeries. Subjects and methods: After taking approval of the hospital ethical committee on research, 30 consenting adult patients, of either sex, of ASA physical status 1 and 2, in the age group of 18-60 years coming for oropharyngeal and maxillofacial surgery were included in the study. After induction of general anaesthesia patients were intubated by conventional nasal intubation technique. Results: When heart rate and mean arterial pressure were compared before and after intubation, significant increase in heart rate and mean arterial pressure were observed. Conclusion : From this study it was concluded that conventional nasal intubation can cause significant change in hemodynamic parameters.